2014
DOI: 10.1115/1.4026576
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model of Aortic Stenosis for the Assessment of Transcatheter Aortic Valve Implantation

Abstract: A significant number of elderly patients with severe symptomatic aortic stenosis are denied surgical aortic valve replacement (SAVR) because of high operative risk. Transcatheter aortic valve implantation (TAVI) has emerged as a valid alternative to SAVR in these patients. One of the main characteristics of TAVI, when compared to SAVR, is that the diseased native aortic valve remains in place. For hemodynamic testing of new percutaneous valves and clinical training, one should rely on animal models. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Accordingly, the mean TPD during systole increases from 12.7 to 42.5 mmHg as the stenosis severity is increased from mild to severe, with important implications on the transmural loads withstood by the heart chambers which are known to increase proportionally. These numerical results in the case of severe AS are in-line with the in-vitro experiments of [40], where a peak jet velocity of 4.9 m/s and mean TPD of 50 mmHg was observed for a HR of 70 bpm. Furthermore, the numerical simulations indicate that a normal cardiac configuration (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, the mean TPD during systole increases from 12.7 to 42.5 mmHg as the stenosis severity is increased from mild to severe, with important implications on the transmural loads withstood by the heart chambers which are known to increase proportionally. These numerical results in the case of severe AS are in-line with the in-vitro experiments of [40], where a peak jet velocity of 4.9 m/s and mean TPD of 50 mmHg was observed for a HR of 70 bpm. Furthermore, the numerical simulations indicate that a normal cardiac configuration (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Current models are capable of recreating diseased 3D tissue in a well-controlled micro-environment to closely mimic pathophysiological condition in cellular density, composition and extracellular matrix proteins [67]. Specific diseases such as cardiac hypertrophy, atherosclerosis and aortic stenosis can be mimicked in a 3D tissue engineered environment [6871]. Although these studies do not directly investigate the role of Wnt related signaling, its function is essential to obtain contractile cardiac cells from PSCs.…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 99%
“…They also determined wall-shear stresses (WSSs), oscillatory shear index (OSI), and recirculation lengths for different stenosed cases. Further studies have been reported in Yap et al (2010); Boyd et al (2005); Qiao and Zhang (2014); Chakravarty and Mandal (2000); Maleki et al (2014); Riahi et al (2011); Haghighi et al (2015); Mekheimer and Elkot (2012); Hung and Tsai (1996).…”
Section: Introductionmentioning
confidence: 88%